The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/2175-7860200859208
|View full text |Cite
|
Sign up to set email alerts
|

Musgos (Bryophyta) da microrregião do Salgado Paraense e sua utilização como possíveis indicadores de ambientes perturbados

Abstract: RESUMO Foi realizado um estudo dos musgos ocorrentes em diferentes ecossistemas da microrregião do Salgado Paraense, visando determinar a riqueza, registrar os tipos de ecossistemas e substratos de ocorrência das espécies, identificar algumas destas como indicadoras de ambientes perturbados e ampliar o conhecimento da brioflora do estado do Pará. Foram registradas 38 espécies de musgos, distribuídas em 21 gêneros e 11 famílias. A riqueza de espécies foi relativamente baixa, levando-se em consideração a grande … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
3
7
0
2
Order By: Relevance
“…In a study conducted in municipalities of northeastern Pará, Santos & Lisboa (2003) observed that secondary vegetation was one of the environments that presented the highest numbers of records (131) and species (35). In a subsequent study, also conducted in northeastern Pará (Santos & Lisboa 2008), the authors again observed that secondary vegetation presented high numbers of records (336) and species richness (31), as in the present study.…”
Section: Microlejeunea Acutifoliasupporting
confidence: 86%
“…In a study conducted in municipalities of northeastern Pará, Santos & Lisboa (2003) observed that secondary vegetation was one of the environments that presented the highest numbers of records (131) and species (35). In a subsequent study, also conducted in northeastern Pará (Santos & Lisboa 2008), the authors again observed that secondary vegetation presented high numbers of records (336) and species richness (31), as in the present study.…”
Section: Microlejeunea Acutifoliasupporting
confidence: 86%
“…The genera Lejeunea, Cheilolejeunea, Ceratolejeunea, Fissidens, Calymperes and Syrrhopodon are often the most representative in Pará (Santos and Lisboa, 2008;Moraes and Lisboa, 2009;Brito and Ilkiu-Borges, 2013;Moura et al, 2013), and therefore this result was also predictable.…”
Section: Guild Fragmentsmentioning
confidence: 94%
“…Among the most occurring species, Calymperes erosum is considered quite tolerant, and may be potentially indicative of disturbed habitats (Santos and Lisboa, 2008), other species such as Octoblepharum albidum, Taxitelium planum, Sematophyllum subsimplex and Calymperes palisotii which also occurred in the region of the great curve of the Xingu River were considered as indicators of disturbed habitats by Lisboa and Ilkiu-Borges (1995).…”
Section: Guild Fragmentsmentioning
confidence: 99%
See 2 more Smart Citations